Control interno en las auditarías de las compañías obligadas a presentar estados financieros auditados. - Quizhpe Caiminagua, Mayra Delicia (2017)
The present work of qualification, begins with a brief introduction showing the reasons for the interest in developing the agenda item "Report of internal control audits of the companies required to submit financial statements audited in the Ecuador"; declares the need for the study; explains the framework of problem and describes the internal structure of the document. Chapter one presents an overview of the purpose of the study, which is defined and it contextualizes internal control audit report, investigating in three scientific articles the NIA 400, audit planning and the presentation of the Charter of internal control; the interesting fact that has work stressing that the flow of management information must give timely replies in the decision-making process, describes the problem, its causes and effects; drafting a prognosis of the object of study related to relevance to the presentation of the Charter of internal control; arises the objective of the research by formulating the problem in question to establish the objective of the analysis of the case, logically connected. In chapter two, is a description of the epistemological approach to the object of study (internal control in enterprises), describing the accounting as the angular part of the commercial law; the commitment of all members of an organization to ensure compliance with the objectives of internal control; history of the COSO report on the definition of internal control; Describes the theoretical research bases, such as: definition and responsibility for internal control; report COSO, ERM (integrated framework for business risk management); the eight components of the COSO, ERM: environmental control, establishment of objectives, identification of events, risk, response to the risk assessment, control, information and communication, and supervision; risks: risk of audit inherent risk, control risk and detection risk; evaluation of internal control; and the report of internal control in the process of the audit. Chapter three describes the methodological process, pointing to the selected research design, which explains of the because our research is applied and explanatory; narrates the process of collecting data in research: unit of analysis, population, size and selection of the sample, which was made randomly on a basis of 100 professionals and corporate executives; and described the system of categorization in the analysis of the data. In chapter four of case analysis are given to know the results of the research, presenting four data tables and four graphics; two quantitative and two qualitative tables, an analysis was performed by each graphic of the results of the interviews and surveys made to business and professional executives from the field of the object of study; Finally three findings were presented with their respective recommendations, highlighting the legal regulations and the omission in the contracts, as factors that influence the non-submission of the report of internal control at the end of the planning in the process of the audit to the financial statements that senior management take corrective actions in a timely manner and the goal namely, preparing and presenting reasonable financial statements.